(3GdgOGjI aj GdfMhs - (3GHf OQSJhjI, YHO Gddg Hf LYaQ Hf OQSJhjI, J(B347(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO agPG eNJUQ eVHhW aj Yde GdfMh LeYJ ajg egeGJ GdfMh hQJHJg Ydi JQJjH GdcGajI hSejJg GdgOGjIs
(3BNQgG (B:s
(3SGcfI dGdJbGA GdSGcfjf Ef dRe GdJbGA GdSGcfjf Ydi ZjQ MOg hgh hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 76s
(3eYLe GdeDdajf(B: 2 / 233s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs